1999
DOI: 10.7589/0090-3558-35.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Selected Infectious Disease Agents in Raccoons From Illinois

Abstract: The determination of serologic titers to infectious organisms is a valuable tool for quantitating exposure to disease organisms. Raccoons (Procyon lotor) were live-trapped from September 1989 to October 1993 and samples collected from two distinct locations in west-central Illinois (USA); a state recreational facility (Park) and privately owned farming property (Farm). Sera were submitted for testing Leptospira interrogans (serovars bratislava, canicola, grippotyphosa, hardjo, icterohemmorhagiae, and pomona), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
44
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 18 publications
(30 reference statements)
13
44
1
2
Order By: Relevance
“…The overall seroprevalence of the leptospiral infection in raccoons in this study was 46.1%, which is generally comparable to the other studies in North America such as 50% in Maryland (Alexander et al 1972), 58.8% in Georgia (Shotts et al 1975), 48% in Illinois (Mitchell et al 1999), 45% in Illinois (Hungerford et al 2000), 36% in Connecticut (Richardson & Gauthier 2003), 11% in Nebraska (Bischof & Rogers 2005), 19.1% in Washington (Davis et al 2007) and 47% in Indiana (Raizman et al 2009). However, the serological results may greatly underestimate infection with leptospiral serovars in the reservoir hosts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The overall seroprevalence of the leptospiral infection in raccoons in this study was 46.1%, which is generally comparable to the other studies in North America such as 50% in Maryland (Alexander et al 1972), 58.8% in Georgia (Shotts et al 1975), 48% in Illinois (Mitchell et al 1999), 45% in Illinois (Hungerford et al 2000), 36% in Connecticut (Richardson & Gauthier 2003), 11% in Nebraska (Bischof & Rogers 2005), 19.1% in Washington (Davis et al 2007) and 47% in Indiana (Raizman et al 2009). However, the serological results may greatly underestimate infection with leptospiral serovars in the reservoir hosts.…”
Section: Discussionsupporting
confidence: 87%
“…Serogroups Canicola, Grippotyphosa and Sejroe were found in raccoons in Indiana in the present study; serogroup Grippotyphosa was predominant. One study reported previously has also shown that the raccoons act as the natural reservoir for L. interrogans, especially serovar Grippotyphosa (Shotts et al 1975;Mitchell et al 1999). Therefore, a large sampling of raccoons in Indiana for the surveillance of leptospirosis around the residential and livestock area may reveal leptospiral serovars involved in zoonotic or public health concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…North American raccoons (Procyon lotor) have been shown to carry leptospires in their kidneys in the United State [17] and serum antibodies against leptospires have been detected in raccoons in the United States and Canada [13,14,17,19]. It has been reported that trappers of raccoons contracted leptospirosis in Canada [19].…”
mentioning
confidence: 99%
“…The analysis of data in the cross-sectional studies was almost always performed on the basis of exposure rather (Mitchell et al, 1999).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%